2011
DOI: 10.1016/j.jphotochem.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced coloration of 2-hydroxychalcone in the clay interlayer

Abstract: 2-hydroxychalcones are known to be converted to the colored flavylium form under UV irradiation. In this study, the photochemical conversion of two 2-hydroxychalcone derivatives (4'-dimethylamino-2-hydroxychalcone and 4'-methoxy-2-hydroxychalcone) has been carried out in the solid matrix by the intercalation into the layer of the clay, montmorillonite. The 2-hydroxychalcone has been adsorbed on the clay by modifying the clay interlayer with a cationic surfactant, dodecyltrimethylammonium chloride. The addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Some details of anthocyanin chemistry could be fully understood only after achievements obtained by the study of synthetic flavylium analogues . On the other hand, flavylium derivatives can perform as photochromic systems, both in solution and in more organized matrices, as well as models for the development of optical memories …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some details of anthocyanin chemistry could be fully understood only after achievements obtained by the study of synthetic flavylium analogues . On the other hand, flavylium derivatives can perform as photochromic systems, both in solution and in more organized matrices, as well as models for the development of optical memories …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Some details of anthocyanin chemistry could be fully understood only after achievements obtained by the study of synthetic flavylium analogues. [5,6] On the otherh and, flavyliumd erivatives can perform as photochromic systems, [1,7,8] both in solutiona nd in more organizedm atrices, [9][10][11][12][13] as well as models for the developmento fo pticalm emories. [1,14] One interestingc haracteristic of flavylium derivatives is the existence of ac ommon sequence of chemicalr eactions, as shown in Scheme1 for malvidin-3-O-glucoside (oenin).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that various dyes could be stabilized by their adsorption into the interlayer of clays 7,8,12,13) or pores of MPS 3,9,10) . However, AD dyes tend to decompose more easily than AN dyes as the sugar chain from anthocyanin has been removed by hydrolysis in the former.…”
mentioning
confidence: 99%
“…A similar behavior has been shown by the 2-hydroxychalcones dye (HC), which is converted to the colored flavylium form (FV) under UV irradiation [31]. The immobilization of HC dyes within clay lamellae affects the photochromic response depending on the polarity of the interlayer space as well as the acidity by considering that the FV form prefers the polar environment.…”
Section: Cationic Clay Thermoplastic Polymer Sensorsmentioning
confidence: 64%